PEMIKIRAN IMAM AL-GHAZALI DALAM ILMU ADMINISTRASI NEGARA - Wisber Wiryanto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2022)
Imam al-Ghazali (1058-1111) was a classical Muslim scholar and the author of the Ihya' Ulumiddin books which contains both naqli and aqli branches of science, and an explanation of the maintenance of government power including the sultan's properties, his entry and granting of halal and haram; as well as amar-ma'ruf and nahi munkar against him. So it can be assumed, the Ihya’ Ulumiddin also contains concepts and categories that are relevant to the public administration contemporary. Therefore, a study was conducted with a problem formulation, how did Imam al-Ghazali’s thoughts on public administration science? The research objective was to identify the concepts of Imam al-Gazali’s thoughts on public administration science in Ihya' Ulumiddin. Research methods using library research with a qualitative descriptive approach. The source of data is Ihya' Ulumiddin, as for the focus of research is the public administration. Data collection using a deductive-inductive technique. Next, the data are discussed using a synthesis analysis technique for making conclusions. The research was conducted in 2020. The results are shown, that the concept of Imam al-Ghazali's thought on public administration science in the discussion of government administration, covering halal and haram income and expenditure, organizational of government officials, personnel and salary, leadership and managing, as well as the concept of good governance is determined by dynamics among sultan, judges, ulemas and the people through the enforcement of amar ma'ruf and nahi munkar. The concept was relevant to contemporary public administration, then it needs to be applied to realize good governance.